Evolutionary and functional characterization of lagomorph guanylate-binding proteins: a story of gain and loss and shedding light on expression, localization and innate immunity-related functions - Luca Schelle; João Vasco Côrte-Real; João Vasco Côrte-Real; João Vasco Côrte-Real; João Vasco Côrte-Real; Sharmeen Fayyaz; Sharmeen Fayyaz; Augusto del Pozo Ben; Margarita Shnipova; Moritz Petersen; Rishikesh Lotke; Bhavna Menon; et al. (Frontiers in Immunology, 2024)
Guanylate binding proteins (GBPs) are an evolutionarily ancient family of proteins that are widely distributed among eukaryotes. They belong to the dynamin superfamily of GTPases, and their expression can be partially induced by interferons (IFNs). GBPs are involved in the cell-autonomous innate immune response against bacterial, parasitic and viral infections. Evolutionary studies have shown that GBPs exhibit a pattern of gene gain and loss events, indicative for the birth-and-death model of evolution. Most species harbor large GBP gene clusters that encode multiple paralogs. Previous functional and in-depth evolutionary studies have mainly focused on murine and human GBPs. Since rabbits are another important model system for studying human diseases, we focus here on lagomorphs to broaden our understanding of the multifunctional GBP protein family by conducting evolutionary analyses and performing a molecular and functional characterization of rabbit GBPs. We observed that lagomorphs lack GBP3, 6 and 7. Furthermore, Leporidae experienced a loss of GBP2, a unique duplication of GBP5 and a massive expansion of GBP4. Gene expression analysis by reverse transcriptase quantitative polymerase chain reaction (RT-qPCR) and transcriptome data revealed that leporid GBP expression varied across tissues. Overexpressed rabbit GBPs localized either uniformly and/or discretely to the cytoplasm and/or to the nucleus. Oryctolagus cuniculus (oc)GBP5L1 and rarely ocGBP5L2 were an exception, colocalizing with the trans-Golgi network (TGN). In addition, four ocGBPs were IFN-inducible and only ocGBP5L2 inhibited furin activity. In conclusion, from an evolutionary perspective, lagomorph GBPs experienced multiple gain and loss events, and the molecular and functional characteristics of ocGBP suggest a role in innate immunity.